Joint flexion/extension angle estimation using ultra-wideband (UWB) radios - Liu, Hao (2014)
Joint flexion/extension angle parameter is essential for investigating complex gait disorders, and monitoring of process in rehabilitation. This is very important for medical applications. There are many methods to measure the joint flexion/extension angle. Comparing with other measuring methods, wearable Ultra Wideband (UWB) radio is good candidate for human motion tracking due to its high ranging and positioning accuracy, low cost, less power consumption and robust performance in various environments.